MENFORMULASI PENDIDIKAN PESANTREN YANG MEMBEBASKAN - M. Muhlis Sholichin (Institut Agama Islam Negeri Madura)
AbstractIslam is a religion of liberation due to the fact that Islam appreciates human to be in equal level, maintains humanity, and higly supports the values democration and justice, teaches telling the truth, and loves the poor and the oppressed. Thus, Islamic education ideally could be conducted on the basis of equality and human dignity. This is to get rid of external hegemony an dit is to give priority to rightness, honesty and fairness, sincerity, and simplicity. The educational foundation might be used by the peasantren (Islamic boarding school) for the instrcutional practice. It is derived from the values that are developed through the educational process—independency, simplicity, and sincerity. The values become the armor for pesantren to get free from any kinds of life anomaly as the impact of the hegemony of modern life style and paradigm. This view concerns with materialism, hednism, opportunism, individualism, and consumerism.Kata-kata kunciPendidikan, pesantren, pembebasan